Capacitor bank placement in radial distribution system using particle swarm optimization algorithm - Muhammad Naufal Charles Abdullah (2023)
Power system consists of generations, transmission lines, distributions and loads. At the distribution level, 13% of the total generated power consists of real and reactive power losses due to the predominantly inductive nature of loads and distribution feeders as well as transformers and lines which account for substantial portion of power losses caused by lagging currents. In order to show reduction in the reactive power loss and improvement of voltage profile at distribution system, capacitor banks with optimised size placed at identified weak buses has been proposed. Two cases are performed namely base case and reactive power contingency case and implemented on the IEEE 30 bus system adapted with distribution voltage levels. The base case is analysed in PSS/E software to provide a benchmark on the power losses and voltage profile as well as to identify candidate weak buses using normalised value of voltage. Then, a reactive power contingency is carried out to ascertain the appropriate capacitor sizing using QV sensitivity analysis.